车网耦合系统低频振荡建模系统及分析方法 (2022)
本发明公开了一种车网耦合系统低频振荡建模系统及分析方法，基于改进描述函数法，建立LLC变换器输入阻抗模型；用LLC变换器输入阻抗模型结合基于状态空间平均法的级联H桥四象限整流器模型，建立电力电子牵引变压器机车等效阻抗模型；根据电力电子牵引变压器机车等效阻抗模型，采用奈奎斯特判据判断车网系统稳定性，设置对照实验分析电力电子牵引变压器车网系统的低频振荡机理和影响因素。本发明基于改进描述函数法有效分析出车网耦合系统的低频振荡机理和影响因素。 The invention discloses a vehicle network coupling system low-frequency oscillation modeling system and an analysis method. The method comprises the following steps: building an LLC converter input impedance model based on an improved description function method; combining the LLC converter input impedance model with a cascaded H-bridge four-quadrant rectifier model based on a state space averaging method to establish a power electronic traction transformer locomotive equivalent impedance model; According to the equivalent impedance model of the power electronic traction transformer locomotive, judging the stability of the locomotive network system by adopting a Nyquist criterion, and setting a contrast experiment to analyze a low-frequency oscillation mechanism and influence factors of the po